2019
DOI: 10.1002/dneu.22708
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced generation of intraluminal vesicles in neuronal late endosomes in the brain of a Down syndrome mouse model with endosomal dysfunction

Abstract: Down syndrome (DS) is a human genetic disease caused by trisomy of chromosome 21 and characterized by early developmental brain abnormalities. Dysfunctional endosomal pathway in neurons is an early event of DS and Alzheimer's disease. Recently, we have demonstrated that exosome secretion is upregulated in human DS postmortem brains, in the brain of the trisomic mouse model Ts[Rb(12.1716)]2Cje (Ts2) and by DS fibroblasts as compared with disomic controls. High levels of the tetraspanin CD63, a regulator of exos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…Recent findings argue that it is brain exosome production, and more specifically neuronal exosome production, which is higher in DS compared to diploid controls. Using high-resolution electron microscopy and quantitative analyses of MVBs in neurons of the frontal cortex of Ts2 mice, we recently showed that Ts2 MVBs are larger, more abundant, and contain a higher number of ILVs per neuron compared to littermate diploid controls (D'Acunzo et al, 2019). While not neuron specific, higher levels in Ts2 mice compared to controls of ILV proteins within the brain subcellular fractions that also contained endosomal markers corroborated these electron microscopy findings (D'Acunzo et al, 2019).…”
Section: Exosome Secretion Is Enhanced In the Ds Brainmentioning
confidence: 78%
“…Recent findings argue that it is brain exosome production, and more specifically neuronal exosome production, which is higher in DS compared to diploid controls. Using high-resolution electron microscopy and quantitative analyses of MVBs in neurons of the frontal cortex of Ts2 mice, we recently showed that Ts2 MVBs are larger, more abundant, and contain a higher number of ILVs per neuron compared to littermate diploid controls (D'Acunzo et al, 2019). While not neuron specific, higher levels in Ts2 mice compared to controls of ILV proteins within the brain subcellular fractions that also contained endosomal markers corroborated these electron microscopy findings (D'Acunzo et al, 2019).…”
Section: Exosome Secretion Is Enhanced In the Ds Brainmentioning
confidence: 78%
“…Exosomes are the small-size subtype of EVs associated with endosomal biogenesis pathways [ 35 ]. The formation of exosomes starts with the inward budding of early endosomal membrane which creates intraluminal vesicles [ 36 ]. The generation of these intraluminal vesicles in endosomes is known to be highly regulated by endosomal sorting complex required for transport (ESCRT) complexes.…”
Section: Biogenesis and Classification Of Evsmentioning
confidence: 99%
“…4 Accordingly, our previous research has supported a beneficial role for EVs in vulnerable neurons with endosomal pathology, one of the earliest insults observed in Alzheimer's disease (AD), 5 by relieving the cells from toxic waste that was not efficiently degraded intracellularly. 6,7 However, the identification of full-length amyloid-β precursor protein (flAPP) and amyloid-β precursor protein (APP) metabolites in EVs [8][9][10][11] has implicated EVs in AD amyloid pathology by carrying and spreading pathology throughout the brain. The accumulation of the amyloid-β (Aβ) peptide in extracellular senile plaques is one of the pathological hallmarks of AD.…”
Section: Introductionmentioning
confidence: 99%